A systematic literature review of process modeling guidelines and their empirical support. Issue 1 (7th November 2020) - Avila, Diego Toralles; dos Santos, Rubens Ideron; Mendling, Jan; Thom, Lucineia Heloisa
Abstract : Purpose: Process modeling guidelines are a valuable instrument for increasing the quality of process models. Since finding and selecting suitable guidelines are challenging, this paper aims to find and select suitable guidelines because they are scattered across the many studies of the literature. Also, not all of them are supported by empirical studies. Design/methodology/approach: The authors conducted a systematic literature review to collect and analyze process modeling guidelines present in the literature and the empirical evidence that supports them. Findings: The authors investigated a total of 793 articles and identified a total of 45 process modeling guidelines in five different categories. For each of these guidelines, the authors report empirical evidence together with corresponding measures, such as comprehension accuracy and error probability. Originality/value: Compared to the prior literature reviews on process model quality and process modeling guidelines, this article extends current knowledge by analyzing the empirical evidence and variables associated with each guideline. This analysis provides guidance for practitioners and scholars on which guidelines to use while modeling a process and perform further research on.